Peningkatan Pengetahuan dan Keterampilan Petani dalam Menekan Cemaran Aflatoksin pada Jagung Hibrida - Dahlan, Sakinah Ahyani; Sirajuddin, Zulham; Rahman, Rival (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Aflatoxin is a type of fungus that infects corn kernels and can reduce their quality. Aflatoxin contamination can lead to a decline in corn prices at the collector level, negatively impacting farmers' income. To address this issue, efforts are needed to enhance farmers' understanding and skills in cultivation techniques and post-harvest handling to suppress aflatoxin growth. One of the measures taken is training farmers in Good Agricultural Practices (GAP) and Good Handling Practices (GHP). This program aims to expand farmers' knowledge and equip them with proper cultivation techniques and appropriate post-harvest handling methods. The training materials cover aflatoxin control strategies, suitable storage methods, and cultivation practices that help maintain corn quality. The training results indicate that this initiative positively contributes to increasing farmers' awareness and knowledge regarding the importance of applying correct techniques to prevent aflatoxin contamination. By implementing better techniques, farmers are expected to minimize the risk of corn price declines caused by aflatoxin contamination. This can help them maintain price stability and increase their income from higher-quality harvested corn.